Volumetric estimations of the gray matter, white matter and lateral ventricles on the brain hemispheres in horses using cavalieri principle - Sadullah Bahar; M. Orhun Dayan (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine morphometric features of the horse brain hemispheres and to be reference MRI/CT images and measurements which recently started to be used in veterinary field. Materials and Methods: Brains of five horses of different breeds and sexes were used. Volumetric estimations of the gray matter, white matter and lateral ventricles of the cerebrum were performed using Cavalieri principle. Results: In this study, there were no significant differences between volumes of gray matter, white matter, lateral ventricules and the total volumes in the left and the right hemispheres of brain. Conclusions: The volumetric features of the left and the right brain hemispheres in horses were similar. It is thought that obtained data will contribute to the morphology of related region and the further studies.